Exploring the Impact of Verbal Communication Strategies in the Marketing of Fruit Items in Nepalgunj City, Nepal - Adhikari, Shreedhar (Academia Research Journal, 2023)
This research article investigates the effects of verbal communication strategies in the marketing of fruit items in Nepalganj, Nepal. The study aimed to identify the most effective verbal communication strategies that can be used to promote fruit items in Nepalgunj's local market. To achieve this objective, a survey questionnaire was administered to 150 respondents, including customers and vendors of fruit items in Nepalgunj. The study found that verbal communication strategies such as persuasive language, use of humor, and the use of local dialects were the most effective in promoting fruit items in the local market. Additionally, the study revealed that the age and educational level of customers significantly influenced their preferences for verbal communication strategies.